2017
DOI: 10.3390/nano7120455
|View full text |Cite
|
Sign up to set email alerts
|

The Room-Temperature Chemiresistive Properties of Potassium Titanate Whiskers versus Organic Vapors

Abstract: The development of portable gas-sensing units implies a special care of their power efficiency, which is often approached by operation at room temperature. This issue primarily appeals to a choice of suitable materials whose functional properties are sensitive toward gas vapors at these conditions. While the gas sensitivity is nowadays advanced by employing the materials at nano-dimensional domain, the room temperature operation might be targeted via the application of layered solid-state electrolytes, like ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…When deposited on the Au electrode the material represents a rather dense though porous film comprised of interconnected flakes (Figure 1c) architecture which is favorable for gas sensor development due to high surface-to-volume ratio. Therefore, we have applied the same approach to the deposition of cobalt oxide on Si substrate equipped with multiple Pt strips 59 to develop gas-sensitive layers. In preliminary studies, we have not found large differences in the morphology of cobalt oxide when employing the same protocols for deposition at Pt electrodes.…”
Section: Electrochemical Synthesis Of the Functional Layermentioning
confidence: 99%
“…When deposited on the Au electrode the material represents a rather dense though porous film comprised of interconnected flakes (Figure 1c) architecture which is favorable for gas sensor development due to high surface-to-volume ratio. Therefore, we have applied the same approach to the deposition of cobalt oxide on Si substrate equipped with multiple Pt strips 59 to develop gas-sensitive layers. In preliminary studies, we have not found large differences in the morphology of cobalt oxide when employing the same protocols for deposition at Pt electrodes.…”
Section: Electrochemical Synthesis Of the Functional Layermentioning
confidence: 99%
“…In the reaction, the increased charge carriers on semiconductor surfaces will reduce the thickness of the depletion layer there, which will subsequently cause the resistance of the semiconductor to drop [24]. Importantly, the major interest is in discovering options for operating sensors at low temperatures (room temperature) without losing elevated sensing capacity [25,26]. Nonetheless, the sensitivities of their gas are frequently only obtained at high temperatures, resulting in low durability and high energy consumption [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, peculiarities of the generation of carriers and their transfer found a great interest in the chemical sensing where light irradiation could particularly reduce the energy consumption by gas sensors [ 17 , 18 , 19 ]. The primary interest is to find options for the sensor operation at room temperature without a loss in high sensing capacity [ 20 , 21 , 22 ]. Here, the simplest way to create a chemiresistive layer between the flat metal electrodes is sedimentation of oxide nanostructures over the inter-electrode gap.…”
Section: Introductionmentioning
confidence: 99%